Prosodic and segmental aspects of nonword repetition in 4- to 6-year-old children who are deaf and hard of hearing compared to controls with normal hearing. (3rd October 2018) - Sundström, Simon; Löfkvist, Ulrika; Lyxell, Björn; Samuelsson, Christina
ABSTRACT: Children who are deaf or hard of hearing (DHH) are at an increased risk of speech and language deficits. Nonword repetition (NWR) is a potential predictor of problems with phonology, grammar and lexicon in DHH children. The aim of the present study was to examine repetition of prosodic features and segments in nonwords by DHH children compared to children with normal hearing (NH) and to relate NWR performance to measures of language ability and background variables. In this cross-sectional study, 14 Swedish-speaking children with mild–profound sensorineural hearing loss, aged 4–6 years, and 29 age-matched controls with NH and typical language development participated. The DHH children used cochlear implants (CI), hearing aids or a combination of both. The assessment materials included a prosodically controlled NWR task, as well as tests of phonological production, expressive grammar and receptive vocabulary. The DHH children performed below the children with NH on the repetition of tonal word accents, stress patterns, vowels and consonants, with consonants being hardest, and tonal word accents easiest, to repeat. NWR performance was also correlated with language ability, and to hearing level, in the DHH children. Both prosodic and segmental features of nonwords are problematic for Swedish-speaking DHH children compared to children with NH, but performance on tonal word accent repetition is comparably high. NWR may have potential as a clinically useful tool for identification of children who are in need of speech and language intervention.